Dos nuevas especies de Stilestrongylus (Nematoda: Heligmonellidae) parásitos de Peromyscus (Rodentia: Cricetidae) de México - Falcón Ordaz, Jorge (1999)
Slilestrongylus peromysci n. sp. collected from Peromyscus difficilis (Hidalgo state, México), differs from other species in the genus in number of the spines (30 ) in the synlophe (both sexes) and because the eigth ray arises from the root of the ninth ray; S. hidalguensis n. sp. parasited Peromyscus sp. and differs from all other congeneric species in tbe presence of 24 spines in the male synlophe and in the arrangement of the bursal rays (2-2-1 in the right lobe and 2-3 in the left lobe). A key to the species of Stilestrongylus is provided.